GLUT12 promotes prostate cancer cell growth and is regulated by androgens and CaMKK2 signaling. Issue 4 (April 2018) - White, Mark A; Tsouko, Efrosini; Lin, Chenchu; Rajapakshe, Kimal; Spencer, Jeffrey M; Wilkenfeld, Sandi R; Vakili, Sheiva S; Pulliam, Thomas L; Awad, Dominik; Nikolos, Fotis; Katreddy, Rajasekhara Reddy; Kaipparettu, Benny Abraham; et al.
Abstract : Despite altered metabolism being an accepted hallmark of cancer, it is still not completely understood which signaling pathways regulate these processes. Given the central role of androgen receptor (AR) signaling in prostate cancer, we hypothesized that AR could promote prostate cancer cell growth in part through increasing glucose uptake via the expression of distinct glucose transporters. Here, we determined that AR directly increased the expression of SLC2A12, the gene that encodes the glucose transporter GLUT12. In support of these findings, gene signatures of AR activity correlated with SLC2A12 expression in multiple clinical cohorts. Functionally, GLUT12 was required for maximal androgen-mediated glucose uptake and cell growth in LNCaP and VCaP cells. Knockdown of GLUT12 also decreased the growth of C4-2, 22Rv1 and AR-negative PC-3 cells. This latter observation corresponded with a significant reduction in glucose uptake, indicating that additional signaling mechanisms could augment GLUT12 function in an AR-independent manner. Interestingly, GLUT12 trafficking to the plasma membrane was modulated by calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2)-5′-AMP-activated protein kinase (AMPK) signaling, a pathway we previously demonstrated to be a downstream effector of AR. Inhibition of CaMKK2-AMPK signaling decreased GLUT12 translocation to the plasma membrane by inhibiting the phosphorylation of TBC1D4, a known regulator of glucose transport. Further, AR increased TBC1D4 expression. Correspondingly, expression of TBC1D4 correlated with AR activity in prostate cancer patient samples. Taken together, these data demonstrate that prostate cancer cells can increase the functional levels of GLUT12 through multiple mechanisms to promote glucose uptake and subsequent cell growth.